Dance: Shaping lives through creative movement - Pezer, Daniel (U.K., 2007)
Daniel and Lisa are shining examples of the principles found in this booklet and have a passion to reclaim dance as a godly art form. They describe in detail how to develop a dance ministry in your church and cover both the spiritual and practical aspects of developing disciples through dance.
Keywords: Religious dance